Prevladujoča logika storitve v marketingu - Melink, Nina (Akademija MM, 2014)
The conventional goods marketing has not only been criticized and reconceptualized since its existence, but since the existence of the exchange phenomenon itself. A common denominator of alternative perspectives, usually rejected and politely ignored, is the transition from goods to service as a central focus of exchange. Robert F. Lusch's and Stephen L. Vargo's attempts of service marketing reconceptualizations have resulted in a realization of a bigger service potential for theoretical and practical implications of marketing and other related disciplines. Based on the existent, but overlooked theoretical background, they've formed a new logic, called service-dominant logic, which is the main focus of this paper. The method used to form the presentation is a systematic literature review, which allows identification of key conceptual evolutions through scientific articles, starting with "Evolving to a New Dominant Logic for Marketing", the first article published establishing a theoretical framework for service-dominant logic. The goal of this paper is to offer a fresh perspective to Slovenian marketing thought, which challenges mainstream theoretical and practical frameworks of goods marketing and emphasizes the need for a better solution to existent conditions, based on more dynamic and progressive, costumer-oriented organizational thinking and activities with broader social implications.
Keywords: marketing; trženje; tržno komuniciranje